PEMANFAATAN KARTU HURUF DALAM MENINGKATKAN KEMAMPUAN MEMBACA DI KELAS 2 SDK JOGE - Efrida ita; Maria Yasinta Fono, Maria Natalia Defatima Tai (ADISAM PUBLISHER, 2025)
This research aims to improve students' reading skills through the use of letter cards at SDK Joge. This type of research uses a qualitative descriptive type with data collection methods in the form of observation, documentation interviews. The subjects in this research were all students at SDK Joge. The results of this research show that learning activities using letter cards for grade 2 students at SDK Joge have increased. This can be seen from the results of observations that there are several students who have difficulty reading. Reading difficulties in grade 2 students are caused by students who cannot yet distinguish letters of the alphabet, for example